Clinical value of 3D SPECT/CT imaging for assessing jaw bone invasion in oral cancer patients. Issue 7 (July 2019) - Miyashita, Hidetaka; Nakahara, Tadaki; Asoda, Seiji; Kameyama, Kaori; Kawaida, Miho; Enomoto, Reiko; Shiba, Hideyuki; Jinzaki, Masahiro; Kawana, Hiromasa; Nakagawa, Taneaki
Abstract: Purpose: This study compared the diagnostic accuracy of jaw bone invasion (JBI) of oral cancer observed with three-dimensional (3D) SPECT/CT, CT, and MRI, and evaluated the clinical advantages of 3D SPECT/CT compared to conventional two-dimensional (2D) SPECT/CT. Materials and methods: From April 2014 to January 2018, consecutive 16 oral cancer patients with suspected JBI, who had preoperatively undergone the imaging tests, were retrospectively enrolled. The likelihood of JBI was independently scored by a radiologist and oral surgeon. Using 2D or 3D SPECT/CT images, 20 oral surgeons delineated virtual surgical areas on 3D-printed jaws for 3 cases in which the extent of JBI was fully pathologically confirmed. The surgeons completed questionnaires regarding surgical planning and explanations for patients using Likert scales. Results: JBI was found in 9 patients including 5 (56%) with initial bone invasion. 3D SPECT/CT showed very high negative predictive value (100%) and inter-observer agreement (kappa = 0.917). 3D SPECT/CT was more sensitive than CT and MRI when inconclusive findings for JBI were considered negative. Compared to 2D SPECT/CT, 3D SPECT/CT had greater clinical advantages such as surgical planning and explanation to patients (p < 0.005). Conclusion: 3D SPECT/CT is useful not only for detecting JBI but also for surgical planning. Highlights: 3D SPECT/CT is a novel technique that can be used for diagnosing jaw bone invasion. The advantage of 3D over 2D SPECT/CT for surgical planning of jaw bone invasion. 3D SPECT/CT for explaining the details and necessity of jaw surgery to patients.